Respuesta :

Answer:

The function in the form of fog(x) is written as  48 x² + 336 x +  590

Step-by-step explanation:

Given function as :

f(x) = 3 x² - 6 x + 5

g(x) = - 4 x - 13

So, The function in the form of fog(x) is written as

We, substitute the value of g(x) into f(x)

fog(x) = 3 (g(x))² - 6 (g(x)) + 5

Or, fog(x) = 3 (- 4 x - 13 )² - 6 ( - 4 x - 13 ) + 5

or,  fog(x) = 3 (16 x² + 169 + 104 x) + 24 x + 78 + 5

or , fog(x) = 48 x² + 507 + 312 x + 24 x + 78 + 5

or , fog(x) = 48 x² + 336 x +  590

So, The function in the form of fog(x) = 48 x² + 336 x +  590

Hence The function in the form of fog(x) is written as  48 x² + 336 x +  590 Answer